Evaluation of a Web-based Psychosocial Education and Peer Support Program for Alcohol Use Concerns. Issue 3 (3rd July 2021) - Moskal, Dezarie; Whitaker, Holly; Bernstein, Julia F.; Maisto, Stephen A.; Connors, Gerard J.
ABSTRACT: This outcomes assessment was implemented to evaluate a web-based alcohol use recovery program, Tempest Sobriety School (TSS), and to provide a model for outcome evaluation. Adults ( N = 541) enrolled in TSS were assessed at pre-program start and Month 2, 6, and 12. Participants reported decreased alcohol use, drug use, craving for alcohol, and alcohol use disorder symptoms over the course of the program; changes were maintained at Month 6 and 12. Participants reported sustained increases in overall physical and mental health and quality of life. Findings will inform TSS students and stakeholders and provide a model for others conducting similar evaluations.